2021
DOI: 10.1371/journal.pone.0255841
|View full text |Cite
|
Sign up to set email alerts
|

Self-collection of capillary blood using Tasso-SST devices for Anti-SARS-CoV-2 IgG antibody testing

Abstract: Background Efforts to minimize COVID-19 exposure during the current SARS-CoV-2 pandemic have led to limitations in access to medical care and testing. The Tasso-SST kit includes all of the components necessary for remote, capillary blood self-collection. In this study, we sought to investigate the accuracy and reliability of the Tasso-SST device as a self-collection device for measurement of SARS-CoV-2 IgG antibodies. Methods Capillary blood was obtained via unsupervised and supervised application of the Tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 8 publications
(6 reference statements)
4
61
1
Order By: Relevance
“…The feasibility and advantages of sending dried blood spots by mail have been shown in previous epidemiological studies [40][41][42]. The COVID-19 pandemic has further contributed to the increased community acceptance around sending biospecimens in the form of wet blood samples through the mail [13,43].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The feasibility and advantages of sending dried blood spots by mail have been shown in previous epidemiological studies [40][41][42]. The COVID-19 pandemic has further contributed to the increased community acceptance around sending biospecimens in the form of wet blood samples through the mail [13,43].…”
Section: Discussionmentioning
confidence: 90%
“…Increasing pluri-potency of the device (e.g., expanding its use to CD4 count or other regular tests) would augment acceptability, since CD4 testing is recommended once every two weeks along with weekly viral load testing during the initial weeks of ATIs [1,45]. The device was successfully utilized recently to test individuals for COVID-19 antibodies [43].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, self-collection of the blood in the UA group was impaired as patients were requesting help to press the button (5/25; 20%) and to remove the blood collection container (3/25; 12%). Using the same upper-arm device, healthy participants were able to successfully draw blood more often during the first draw and without assistance in a previous study [ 28 ] (first draw: 93 vs 80%; second draw 7 vs 16%). Future studies should analyze the failure rate longitudinally, as experienced users might use these devices more successfully.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, also Blicharz and colleagues reported a significantly lower pain score associated with a similar upper arm device (TAP; Seventh Sense Biosystems, Medford, USA) compared to venous blood collection (0.4 vs 1.5 on pain scale from 0 to 10) investigating 143 participants [ 13 ]. A recent study evaluating the same upper-arm device also showed high correlation between venous and capillary blood when testing for anti-SARS-CoV-2 antibodies [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Capillary blood (100–400 μL) was collected from the upper arm using two types of automated collection devices, one purchased from Seventh Sense Biosystems (Medford, MA), and one purchased from Tasso, Inc. (Seattle, WA). The TAP I blood collection device (Blicharz et al 2018 ) from Seventh Sense Biosystems is designed to collect up to approximately 130 μL over a period of 1–3 min, and the Tasso+ device manufactured by Tasso, Inc. (Hendelman et al 2021 ) can collect up to approximately 400 μL in 5 min. These devices were used according to the manufacturers’ instructions.…”
Section: Methodsmentioning
confidence: 99%